Laudatory speeches for "Fernando de Terán and Joan Busquets" - Medalla de Oro de la Arquitectura 2025 - Ezquiaga, José María; González Cebrián, José (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2025)
The Higher Council of Spanish Architects’ Associations (CSCAE) awarded the GOLD MEDAL FOR ARCHITECTURE 2025, ex aequo, to architects FERNANDO DE TERÁN (Madrid, 1941) and JOAN BUSQUETS (Barcelona, 1946). At the ARCHITECTURE AWARDS 2025 gala, held at the Fernán Gómez Theater in Madrid on July 3rd, the architects and urban planners José María Ezquiaga and José González-Cebrián prepared and read the respective Laudatory speeches for the two awardees. In fair recognition of the professional and academic careers of architects Fernando de Terán and Joan Busquets, we present on these pages the full texts of these presentations.